2018
DOI: 10.1177/2325967118788280
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Parameters at 1 Year Correlate With Clinical Outcomes Up to 17 Years After Autologous Chondrocyte Implantation

Abstract: Background:The ability to predict the long-term success of surgical treatment in orthopaedics is invaluable, particularly in clinical trials. The quality of repair tissue formed 1 year after autologous chondrocyte implantation (ACI) in the knee was analyzed and compared with clinical outcomes over time.Hypothesis:Better quality repair tissue and a better appearance on magnetic resonance imaging (MRI) 1 year after ACI lead to improved longer-term clinical outcomes.Study Design:Cohort study; Level of evidence, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 29 publications
4
48
0
Order By: Relevance
“…Long-term follow-up studies have demonstrated hyaline-like cartilage formation and satisfactory clinical outcome up to 20 years post-surgery ( Brittberg, 2008 ; Peterson et al, 2010 ). Nevertheless, a major part of treated patients shows signs of fibrocartilage formation in the regenerated area ( McCarthy et al, 2018 ). As fibrocartilage is mechanically inferior to hyaline cartilage, it is unfit to fulfill the natural functions of hyaline cartilage and therefore more prone to degradation ( Messner and Maletius, 1996 ; Knutsen et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term follow-up studies have demonstrated hyaline-like cartilage formation and satisfactory clinical outcome up to 20 years post-surgery ( Brittberg, 2008 ; Peterson et al, 2010 ). Nevertheless, a major part of treated patients shows signs of fibrocartilage formation in the regenerated area ( McCarthy et al, 2018 ). As fibrocartilage is mechanically inferior to hyaline cartilage, it is unfit to fulfill the natural functions of hyaline cartilage and therefore more prone to degradation ( Messner and Maletius, 1996 ; Knutsen et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason being that ultimately, how the patient feels about their knee function, is the most important clinical observation and metric of treatment success/failure. Moreover, several studies have shown that there is no correlation between subjective functional outcome such as Lysholm score and objective measures such as histological analyses 23,24 . We have taken measures to help to reduce the limitations associated with the use of subjective scores, including for comparison objective measures (clinical imaging scores) and where possible, histological observations.…”
Section: Discussionmentioning
confidence: 99%
“…We were not only able to report on early findings but also to follow up our patients over an extended time. For example, we reported that at one year, magnetic resonance imaging (MRI) of the operated joint and histology of the repair tissue could be used to monitor early success in 2003 [34] as well as predicting the long-term success for an even larger cohort 17 years later in 2018 [35]. With histological, immunohistochemical and detailed glycan analysis approaches we were able to build a picture of key ECM markers such as collagen [36] and GAGs within the repair tissue [37,38].…”
Section: The 20-year Evolution Of Aci From Pilot Study To Long-stamentioning
confidence: 99%